PENGARUH KUALITAS AUDIT DAN INTEGRATED REPORTING TERHADAP RELEVANSI NILAI DENGAN VARIABEL PEMODERASI ETIKA BISNIS - Puspitasari, Indah; Atiningsih, Suci (STIE PENA, 2024)
This study aims to analyze the influence of audit quality and integrated reporting on value relevance, with business ethics as a moderating variable. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022. A sample of 67 companies was obtained through purposive sampling technique, resulting in 201 research data. Hypothesis testing method used panel data regression with Random Effect Model approach, and for testing the moderating variable used Moderated Regression Analysis (MRA) model. Data analysis was conducted using Eviews version 12. The results of the study show that audit quality does not have a effect on value relevance, integrated reporting has a negative and significant effect on value relevance, the results of the Moderated Regression Analysis (MRA) in the study indicate that business ethics does not have the ability to moderate or weaken the influence of audit quality on value relevance, business ethics as a moderating variable weakens the influence of integrated reporting on value relevance as the dependent variable